COMPOSITION OF THE VOLATILE METABOLITES FROM DIFFERENT PARTS OF TORILIS LEPTOPHYLLA (L.) REICHB. AND T. UCRANICA SPRENGEL - Ã–zek, T.; Ã–zek, G.; Pimenov, M. G.; Kljuykov, E. V.; Baser, K. H. C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The volatile metabolites obtained from different aerial parts of Torilis leptophylla (L.) Reichb. and T. ucranica Sprengel (Umbelliferae) were analyzed by GC-FID and GC/MS methods. Plants were collected at the end of June 2007 in the Eskisehir province of the Central Anatolian region of Turkey. The leaves, fruits and flowers were separately subjected to micro-distillation, using an Eppendorf MicroDistiller to obtain volatile metabolites. The leaf and fruit volatiles of T. leptophylla were characterized by high percentages of myrcene (8.9% and 15.6%, respectively), germacrene D (13.9% and 13.7%, resp.) and spathulenol (6.5% and 3.6%, resp.). The leaf and flower volatiles of T. ucranica were characterized by high amounts of sesquiterpenes with germacrene D (31.7% and 27.5%, resp.), ß-ylangene (6.8% and 5.9%, resp.) and bicyclogermacrene (5.3% and 6.9%, resp.) as major constituents. Among the fruit volatiles of T. ucranica himachalene-type sesquiterpenes, namely 1-á-H-himachal-4-en-1-ß-ol (50.6%), ß-himachalene (10.2%) and 1-himachalen-7-ol (0.8%) were predominant. The major monoterpene of the flowers and fruits of T. ucranica was found to be ß-pinene (15.1% and 11.3%, resp.). To the best of our knowledge, this is the first report on the volatiles of T. ucranica.